Improved viability of probiotics encapsulated in soybean protein isolate matrix microcapsules by coacervation and cross-linking modification. (May 2023) - Hu, Ronghai; Dong, Dejun; Hu, Jielun; Liu, Huan
Abstract: The objective of this research was to encapsulate probiotic bacteria based on soy protein isolate (SPI) matrix using either coacervation, cross-linking modification or their combination, and investigate the influences on the survival of probiotic bacteria during spray drying, in vitro gastrointestinal digestion, heating, UV irradiation and storage. A probiotic isolate Lactobacillus plantarum 550 was spray dried in SPI solution combined with either pectin (PEC), transglutaminase (TGase) or their combination. High survival rate and low moisture content were obtained for all the samples. Microcapsules fabricated using either SPI-PEC coacervation or TGase induced cross-linking obtained well cell survival during gastric digestion, heat/UV treatment and storage, however, combination of these two modification methods generated microcapsules with lower cross-linking degree and loose package structure corresponding with significant negative effects to the cell viability during gastric digestion and storage. Among the formulations tested, SPI-PEC microparticles provided the best protection to the probiotic cells, as pectin own well thermal stability and digestion resistibility, could fill the cracks and voids existed in SPI matrix and form hydrogen bond to stabilize cell membrane during processing. In conclusion, the current study demonstrated that SPI based probiotic microcapsules with high structural density and cross-linking degree may provide better protection to adverse external environment. Graphical abstract: Image 1 Highlights: Probiotic microcapsules consisted by TGase induced cross-linking of SPI was successfully prepared by spray drying. Incorporation of PEC into SPI could significantly improve the survival during gastric digestion and storage. SPI based probiotic microcapsules with high structural density and cross-linking degree may provide better protection.